Analisis Ketentuan Hukum dan Penerapan Sistem First to File dalam Kasus Pembatalan Merek Terdaftar - Sebastian Edward Mardianto; R. Rahaditya (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
The development of the times has led to significant growth in goods and services, resulting in the emergence of new works within these fields. However, in certain conditions, this has given rise to issues concerning brand usage, where individuals or business actors intentionally use the trademarks of other registered companies, particularly those that are well-known and large-scale, to gain specific business advantages in unethical ways that conflict with the law. This is exemplified by the case of an Indonesian citizen named Melinda Oktavia, who used the trademark Electro-Voice—a prominent brand from the United States—without obtaining permission from the original company. The analysis of Legal Provisions and the Application of the First-to-File System in Registered Trademark Cancellation Cases aims to examine the legal provisions and the implementation of the first-to-file system in handling foreign trademark cancellation cases, specifically focusing on the Electro-Voice case. This study employs a normative approach. The research findings reveal that the legal protection provided by the Trademark Law in Indonesia is highly relevant but still causes confusion when linked to foreign famous trademarks, particularly given that infringement of foreign trademark rights intersects with international law and can harm the owner financially and in terms of reputation. In the outcome of the Electro-Voice case, the measures taken by the court signal a positive indication that Indonesian law is capable of protecting well-known trademarks.